Associations of plasma total phospholipid fatty acid patterns with feeding practices, growth, and psychomotor development in 6‐month‐old South African infants. Issue 3 (13th January 2019) - Siziba, Linda P.; Baumgartner, Jeannine; Ricci, Cristian; Jacobs, Adriaan; Rothman, Marinel; Matsungo, Tonderayi M.; Covic, Namukolo; Faber, Mieke; Smuts, Cornelius M.
Abstract: The objective of this study was to assess plasma fatty acid (FA) patterns of 6‐month‐old South African infants and to determine their association with feeding practices, growth, and psychomotor development. Plasma total phospholipid FA composition (% of total FAs) of 6‐month‐old infants ( n = 353) from a peri‐urban township was analysed, and principal component and factor analysis were performed to identify plasma FA patterns. Feeding practices, anthropometric measurements, and psychomotor development scores were determined. Four major plasma phospholipid FA patterns were identified: A plant‐based C18 FA, a high n‐6 long‐chain polyunsaturated fatty acids (LCPUFA), a C 16:1 and long‐chain saturated fatty acid (SFA), and a high n‐3 and low n‐6 LCPUFA pattern. Formula feeding was associated with higher, whereas breastfeeding was associated with lower scores for the plant‐based C18 FA and C 16:1 and long‐chain SFA patterns. On the other hand, breastfeeding, the consumption of cow's milk, and the consumption of semisolid foods were associated with higher scores, whereas formula feeding was associated with lower scores for the high n‐6 LCPUFA pattern. Breastfeeding and the consumption of semisolids were also associated with higher high n‐3 and low n‐6 LCPUFA pattern scores. The C16:1 and long‐chain SFA and high n‐3 and low n‐6 LCPUFA patterns were positively associated with psychomotor development scores. In 6‐month‐old South African infants, we identified distinct plasma FA patterns that presumably represent the FA quality of their diet and that are associated with psychomotor development. Our results suggest that breast milk is an important source of n‐6 LCPUFAs and formula‐fed infants may be at risk of inadequate LCPUFA intake.